Honorer ses morts en socialisme, une économie de l’islam kazakh (1960-1980) - Isabelle Ohayon (Revue des Mondes Musulmans et de la Méditerranée)
Honouring the dead with the ritual prescribed by Islam has never ceased to be a social and moral imperative for Kazakh society during the Soviet period. However, the forms of control, institutionalization and repression implemented under Soviet religious policy altered the way funeral practices were conducted. In addition, the material dimension of the ritual performances (remuneration of officiants, organization of meals, etc.), which was an essential concern for the authorities as well as a leverage for regulation, was a permanent challenge for Kazakh societies. Entangled in the constraints of Soviet economic life, made up of shortages and discretionary practices, the management of cemeteries and the organization of funerals required of the communities that they mobilized significant resources. Their respectability was indeed linked to their conforming to customs and their investment in the increasingly ostentatious rites of prodigality. But they also sanctioned the authority of the deceased, derived in particular from his social position in the Soviet statutory hierarchies. Bearning these challenges, the symbolic, social and material space of death thus constituted a place where practices could be deployed autonomously and Kazakh Muslims could be socialized to religion at the time of late Socialism.